Biochanin A feed supplementation alters dynamics of trace gas emissions from lamb urine‐amended soil - Jacobs, Alayna A.; Flythe, Michael D.; Ely, Donald G.; Munoz, Leah; May, John B.; Nelson, Jim A.; Stanton, Victoria; McGrail, Rebecca K.; Pham, Kent; McCulley, Rebecca L. (Journal of environmental quality, 2024)
Sustainable growth in livestock production requires reductions in trace gas emissions on grazing lands. Urine excreta patches are hot spots for accelerated emissions of carbon and nitrogen. Ruminant dietary supplementation with the isoflavone biochanin A (BCA) has been shown to improve cattle weight gain. To determine if BCA supplementation affects urine N excretion and soil trace gas emissions, soil in microcosms was amended with urine from lambs fed 0, 0.45, or 0.90 g BCA day−1. Soil gas emissions were measured over 60 days and analyzed with a linear mixed‐effects model with repeated measures. On 2 days during the incubation, BCA addition across doses significantly reduced nitrous oxide emissions by 73% and methane by 98% compared to urine from non‐dosed lambs. Cumulative ammonia volatilization was significantly reduced by 33% but cumulative nitrous oxide and methane emissions were not. Alterations in trace gas emissions occurred despite no change in urine N content with BCA feed supplementation. A separate laboratory incubation using urine from a non‐supplemented lamb that was exogenously spiked with varying BCA concentrations supported these results: BCA significantly altered ammonia and methane emission dynamics and reduced cumulative nitrous oxide emissions by up to 41%. BCA did not change soil microbial community structure, suggesting alterations to other processes, such as soil enzyme activity, were affecting soil trace gas emissions. Overall, lamb BCA supplementation did not affect urine N but reduced ammonia volatilization, which may contribute to greater sustainability in livestock production systems. Core Ideas Feeding lambs biochanin reduced urine‐amended soil ammonia volatilization and altered nitrous oxide and methane dynamics. Biochanin A did not alter urine N content or soil microbial communities. Dietary supplementation of biochanin A is a new strategy to reduce soil trace gas emissions from livestock grazing systems. Plain Language Summary Livestock waste, especially urine patches in pastures, contribute greenhouse gases to the atmosphere. The soil mediates these emissions, which are subject to the chemical and biological properties of the soil. Livestock can be fed supplements to improve their growth, one of which is biochanin A, an isoflavone found in the legume red clover. When sheep were fed biochanin A, it was excreted in their urine, and we investigated how the presence of biochanin A influences greenhouse gas emissions from urine‐amended soil. We found that soil urine patches from sheep fed biochanin A had altered levels of greenhouse gases (nitrous oxide and methane) and volatilized less ammonia than soil with urine from sheep fed no biochanin A. This study showed that biochanin A supplementation may contribute to greater environmental sustainability for livestock production.